Social entrepreneurship as an object of state regulation - Osypova, Svitlana; Tataryntseva (Kurbatova), Yuliia (Global Scientific Trends, 2023)
Social entrepreneurship as an object of state regulation is researched in the article. In particular, the features of formation and stages of development of social entrepreneurship are investigated. The views of foreign authors on the definition of social entrepreneurship are analysed. Also, the content of definitions of social entrepreneurship of domestic scientists is investigated.
Keywords: state regulation; social entrepreneurship; development; problems solving